A comparative evaluation of mandibular incisor decrowding with coaxial and optiflex arch wires and their load-deflection rates - S Nagalakshmi; G Sriram; K Balachandar; D Dhayanithi (Wolters Kluwer Medknow Publications, 2014)
Aim: The aim of this study is to determine and compare the load-deflection rate of optiflex arch wire with that of coaxial arch wire and to determine and compare the decrowding efficiency of optiflex arch wire with coaxial arch wire within a period of 45 days. Materials and Methods: Load-deflection rates of optiflex and coaxial wires were found using the INSTRON (4300) machine. A steady load was given to the wire to make it deflect, and the load required to deflect the wire for every 1 mm up to 5 mm, were noted and tabulated. A total of 10 patients, 10-25 years of age (seven males and three females) were selected. All patients had angles Class I malocclusion with a crowding discrepancy of 3-9 mm (according to little's index). All patients required first premolar extraction. Pre (0 day) and post (45 th day) treatment study models and lateral cephalograms were taken for all patients and evaluated. Results: Optiflex had a low load-deflection when compared to coaxial wire. Clinically, optiflex and coaxial wire had similar decrowding efficiency. In both, study model and cephalometric analysis, there was no statistically significant value when comparing their mean variables. Conclusion: Optiflex is an appropriate wire for patients seeking esthetics during fixed appliance therapy as it combines esthetics and efficiency by delivering light continuous forces.